Effects of different extraction methods on structural and physicochemical properties of pectins from finger citron pomace. (15th April 2021) - Yu, Min; Xia, Yuandan; Zhou, Mingpeng; Guo, Yueping; Zheng, Jianyong; Zhang, Yinjun
Graphical abstract: Highlights: Extraction methods affected structural and physicochemical properties of pectins. High GalA content was found in pectin extracted using microwave and ultrasound. Improved low-ester pectin yield in less time by alkaline extraction. Viscosity property was related to molecular weight and particle size. Abstract: The functionality and property of pectin are correlated with its structure which is affected by the extraction method used. In this study, three different methods of extracting pectin, the microwave-assisted extraction (MAE), the ultrasonic-assisted extraction (UAE) and the conventional heating extraction (CHE), were used at three different temperatures with both an acid and alkali extraction solution. It was found that temperature mainly influenced pectin yield, while pectin structures and physicochemical properties were affected by the pH condition and extraction technology. The alkali-extraction with MAE and UAE at short time promoted the yield of low-ester pectin. Monosaccharide composition analysis showed a high galacturonic acid (GalA) content in the pectin derived from MAE and UAE. The high viscosity and desirable viscoelastic properties of the acid-MAE pectin were due to its large molecular weight and particle size. The results contribute to our understanding of the association among pectin extraction, structure and properties.